High peatland methane emissions following permafrost thaw: enhanced acetoclastic methanogenesis during early successional stages - Heffernan, Liam; Cavaco, Maria A.; Bhatia, Maya P.; Estop-Aragonés, Cristian; Knorr, Klaus-Holger; Olefeldt, David (Biogeosciences, 2022)
Permafrost thaw in northern peatlands often leads to increased methane (CH4) emissions, but the underlying controls responsible for increased emissions and the duration for which they persist have yet to be fully elucidated. We assessed how shifting environmental conditions affect microbial communities and the magnitude and stable isotopic signature (δ13C) of CH4 emissions along a thermokarst bog transect in boreal western Canada. Thermokarst bogs develop following permafrost thaw when dry, elevated peat plateaus collapse and become saturated and dominated by Sphagnum mosses. We differentiated between a young and a mature thermokarst bog stage (∼ 30 and ∼ 200 years since thaw, respectively). The young bog located along the thermokarst edge was wetter, warmer, and dominated by hydrophilic vegetation compared to the mature bog. Using high-throughput 16S rRNA gene sequencing, we show that microbial communities were distinct near the surface and converged with depth, but fewer differences remained down to the lowest depth (160 cm). Microbial community analysis and δ13C data from CH4 surface emissions and dissolved gas depth profiles show that hydrogenotrophic methanogenesis was the dominant pathway at both sites. However, mean δ13C-CH4 signatures of both dissolved gas profiles and surface CH4 emissions were found to be isotopically heavier in the young bog (−63 ‰ and −65 ‰, respectively) compared to the mature bog (−69 ‰ and −75 ‰, respectively), suggesting that acetoclastic methanogenesis was relatively more enhanced throughout the young bog peat profile. Furthermore, mean young bog CH4 emissions of 82 mg CH4 m−2 d−1 were ∼ 3 times greater than the 32 mg CH4 m−2 d−1 observed in the mature bog. Our study suggests that interactions between the methanogenic community, hydrophilic vegetation, warmer temperatures, and saturated surface conditions enhance CH4 emissions in young thermokarst bogs but that these favourable conditions only persist for the initial decades after permafrost thaw.